2009
DOI: 10.1007/978-3-211-98811-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Pituitary Adenylate Cyclase Activating Polypeptide Is Involved in Suppression of Edema in the Ischemic Brain

Abstract: Pituitary adenylate cyclase activating polypeptide is a pleiotropic neuropeptide. We previously showed that heterozygous PACAP gene knockout (PACAP(+/-)) mice had larger infarct volumes and worse neurological scores after middle cerebral artery occlusion (MCAO). However, the relationship between endogenous PACAP levels and edema in the ischemic brain has not yet been evaluated. In this study, the formation of edema in the ischemic brain as well as cerebral blood flow was compared between PACAP(+/-) and wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…In addition to the neuroprotection, in the present study we also observed that PACAP decreased the significant edema formation in the retina 7 days after irradiation. The mechanism for this is not known, but recently, a similar observation has been made in ischemic brain edema formation (Nakamachi et al 2010). Figure 1 Morphology of representative retinas from control (a) and different treated animals: exposed to diffuse UV-A radiation (b, c, g) and combined with intravitreal PACAP treatment (d, e, f).…”
Section: Discussionmentioning
confidence: 74%
“…In addition to the neuroprotection, in the present study we also observed that PACAP decreased the significant edema formation in the retina 7 days after irradiation. The mechanism for this is not known, but recently, a similar observation has been made in ischemic brain edema formation (Nakamachi et al 2010). Figure 1 Morphology of representative retinas from control (a) and different treated animals: exposed to diffuse UV-A radiation (b, c, g) and combined with intravitreal PACAP treatment (d, e, f).…”
Section: Discussionmentioning
confidence: 74%
“…In vivo, PACAP deficient mice are more vulnerable to experimental autoimmune encephalomyelitis (Tan et al 2009) and display slower recovery after peripheral nerve crush injury (Armstrong et al 2008). It has also been shown that these mice develop larger infarct volume and increased edema in focal cerebral ischemia (Chen et al 2006;Nakamachi et al 2010;Ohtaki et al 2006). This endogenous protective effect of PACAP in ischemic lesions seems to be not restricted to the brain, but similar findings have been described in peripheral tissues.…”
Section: Discussionmentioning
confidence: 96%
“…This is also true for ischemic injuries. Ohtaki and coworkers showed that PACAP KO mice have increased infarct volume in a model of stroke [ 60 ] with increased edema formation [ 61 ]. Similar results were obtained in the retina: in bilateral carotid artery occlusioninduced retinal ischemia PACAP KO mice showed increased tissue damage [ 62 ].…”
Section: Small Intestinal Ischemic Injury In Pacap Knockout (Ko) Micementioning
confidence: 63%